Après nous le déluge? Direct democracy and intergenerational conflicts in aging societies - Wolfgang Maennig; Gabriel M. Ahlfeldt; Malte Steenbeck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
To assess the likely effects of population ageing on the outcomes of direct democracy, we analyze the effect of age on voting decisions in public referenda. To this end, we provide the first quantitative review of the literature and a case study of the Stuttgart 21 referendum on one of the largest infrastructure projects in Germany. The evidence suggests that intergenerational conflicts arising from population ageing will likely be limited to areas in which the net present value differs particularly strongly across generations, such as education and health spending, green energy, and major transport projects. In such instances, however, the effect can be quantitatively relevant, raising the question of whether, as population ageing progresses, decisions should be based on social cost-benefit anal-yses, instead of referenda.
Keywords: D61; D62; H41; 330